Towards an Integrative Theory of Organizational Success and Failure: Previous Research and Future Issues - Flamholtz, Eric G. (Senate Hall, 2003)
This paper provides a survey of research to develop and empirically test of a holistic model of organizational success and failure in entrepreneurial organizations at different stages of growth. It builds upon previous work by Flamholtz (1995) to develop a model of organizational success and failure and by Flamholtz et.al. to assess the models validity empirically (Flamholtz and Aksehirli, 2000; Flamholtz, 2001; Flamholtz and Hua, 2002A, 2002B). The initial model proposes that there are six key factors or "strategic building blocks" of successful organizations, and the six key variables must be designed as a holistic system, which has been termed "The Pyramid of Organizational Development".
Keywords: strategy|organisational development